The Secreted Ribonuclease SRE1 Contributes to Setosphaeria turcica Virulence and Activates Plant Immunity - He, Shidao; Huang, Yufei; Sun, Yanqiu; Liu, Bo; Wang, Suna; Xuan, Yuanhu; Gao, Zenggui (Frontiers in Microbiology, 2022)
Pathogens can secrete a large number of effectors during the plant infection process. Many of these effectors are well known via diverse strategies that regulate plant immunity and promote the effective colonization of pathogens. However, there are few studies on the ribonuclease (RNase) effectors secreted by fungi. In the present study, we discovered a secretable RNase (SRE1) in the secretome of Setosphaeria turcica that was significantly upregulated during the early stages of S. turcica infection in maize. Knockdown of SRE1 significantly reduced the virulence of S. turcica. SRE1 can induce cell death in maize and Nicotiana benthamiana. However, unlike the conventional hypersensitive response (HR) caused by other effectors, SRE1 is not dependent on its signal peptide (SP) or plant receptor kinases (such as BAK1 and SOBIR1). SRE1-induced cell death depends upon its enzymatic activity and the N-terminal β-hairpin structure. This structure allows SRE1 to enter cells causing cytotoxic effects via the degradation of the plant’s RNA. Furthermore, SRE1 increases the resistance of N. benthamiana against pathogenic fungi and oomycetes. In summary, SRE1 contributes to S. turcica virulence and can induce plant cell death as well as activate plant immune responses.